(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Hypothyroidism is a common endocrine disorder that predominantly affects women of reproductive age and is closely associated with menstrual disturbances, ovulatory dysfunction, infertility, and adverse reproductive outcomes. Thyroid hormone deficiency disrupts the hypothalamic–pituitary–ovarian axis and is frequently accompanied by secondary hyperprolactinemia, further impairing reproductive function. This study was conducted at the Khorezm branch of the Republican specialized scientific and practical medical center of endocrinology and aimed to comprehensively evaluate diagnostic approaches and treatment strategies for reproductive disorders in women with hypothyroidism. Patients were stratified into study groups based on thyroid status and reproductive function. The findings confirm that early diagnosis and optimized levothyroxine therapy significantly improve reproductive outcomes.